Does the carbon price in Chinese seven carbon markets converge or not? Based on the Fourier quantile unit root test - Yi-Lung Lee; Zan Zhang; Xiaokun Li; Tsangyao Chang (Energy Reports, 2019)
While previous studies focus on linear unit root test to study the convergence of carbon price in some developed countries and the results might be biased due to the lower power of these linear unit root tests. China provides an interesting arena to investigate its carbon price convergence due to its fast economic development since its inception of open door policy in the late 1970s. In this paper that we use the non-linear quantile unit root test (in terms of Fourier function) to study the convergence of the carbon price in China's seven carbon markets over the period of April 6, 2014 to February 17, 2017 Empirical results from our study demonstrate that the carbon prices in Beijing, Shanghai, Shenzhen, Guangzhou and Hubei carbon market do converge on all quantiles. However, the prices of Chongqing and Tianjin carbon emission markets though converge but only converge under certain quantiles. Apparently, that our empirical have important policy implications for Chinese government conducting carbon dioxide emission reduction policy during its economic development process.
Keywords: 330; Carbon price; Convergence; Fourier quantile; Unit root test